1991
DOI: 10.1007/bf01307526
|View full text |Cite
|
Sign up to set email alerts
|

Role of estrogens and epidermal growth factor in hepatocellular carcinoma (HCC)

Abstract: Estrogen (E) and epidermal growth factors (EGF) receptors were assayed in the liver of nine patients with hepatocellular carcinoma (HCC). Total E and nuclear E receptors were decreased significantly in neoplastic tissue as compared to the levels found in surrounding nonneoplastic tissue. The EGF receptor was decreased also in neoplastic tissue. On the basis of binding data, a decrease in the number but not in affinity of both the E and EGF receptors was found. Keywordsestrogen; epidermal growth factor receptor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 25 publications
1
2
0
Order By: Relevance
“…Due to multiple variants of ERa and ERb, the actual role of wtER in HCC was too complex to be defined. Several studies have reported that the expression of wtER was less in tumor tissues than in adjacent normal tissues [19, 20], which was in line with our findings on wtERa. These results indicate that wtERa may exhibit a protective role in HCC [21].…”
Section: Discussionsupporting
confidence: 93%
“…Due to multiple variants of ERa and ERb, the actual role of wtER in HCC was too complex to be defined. Several studies have reported that the expression of wtER was less in tumor tissues than in adjacent normal tissues [19, 20], which was in line with our findings on wtERa. These results indicate that wtERa may exhibit a protective role in HCC [21].…”
Section: Discussionsupporting
confidence: 93%
“…The early studies used indirect methods of receptor detection based on ligand binding assays. Table 1 gives the details of these studies [13,15,17,[30][31][32][33][34][35][36][37] . These assays were quantitative and measured the amount of receptor in the samples as well as its affinity for the ligand in terms of dissociation constants.…”
Section: Estrogen Receptormentioning
confidence: 99%
“…Our däta suggest that infcreased expression of the v-erb B related sequences upon serial tumour transplantation is due to a selection of ligand-independent tyrosine kinase activity, because these cells should have a growth advantage in vivo. On the other band, the füll length EGF-receptor mRNA seems to be decreased in some human or rat hepatomas (25,26,27). Therefore, the increased formation of v-erb B related gene transcripts suggests an alternative splicing or a selection of deletion mutations of the EGF receptor gene in Morris hepatoma 7777.…”
Section: Discussionmentioning
confidence: 99%